Enzyme effects on extruded diets for dogs with soybean meal as a substitute for poultry by-product meal - Tortola, L. [UNESP]; Souza, N. G. [UNESP]; Zaine, L. [UNESP]; Gomes, M. O S [UNESP]; Matheus, L. F O [UNESP]; Vasconcellos, R. S.; Pereira, G. T. [UNESP]; Carciofi, A. C. [UNESP] (Wiley, 2013)
The effects of exogenous enzymes supplementation on kibble diets for dogs formulated with soybean meal (SBM) as a substitute for poultry by-product meal (PM) was investigated on nutrient digestibility, fermentation products formation, post-prandial urea response and selected faecal bacteria counts. Two kibble diets with similar compositions were used in two trials: PM-based diet (28.9% of PM; soybean hulls as a fibre source) and SBM-based diet (29.9% of SBM). In experiment 1, the SBM diet was divided into three diets: SBM-0, without enzyme addition; SBM-1, covered after extrusion with 7500U protease/kg and 45U cellulase/kg; and SBM-2, covered with 15000U protease/kg and 90U cellulase/kg. In experiment 2, the SBM diet was divided into three diets: SBM-0; SBM-1, covered with 140U protease/kg; 8U cellulase/kg, 800U pectinase/kg, 60U phytase/kg, 40U betaglucanase/kg and 20U xylanase/kg; and SMB-2, covered with 700U protease/kg, 40U cellulase/kg, 4000U pectinase/kg, 300U phytase/kg, 200U betaglucanase/kg and 100U xylanase/kg. Each experiment followed a block design with six dogs per diet. Data were submitted to analysis of variance and means compared by orthogonal and polynomial contrasts (p<0.05). In both experiments, nutrients and energy digestibility did not differ between diets (p>0.05). SBM consumption resulted in increased faecal moisture and production (p<0.05), without effect on faecal score. Higher concentration of propionate, acetate and lactate, and lower ammonia and pH were found in the faeces of dogs fed SBM (p<0.05). Higher post-prandial urea was verified in dogs fed SBM (p<0.05). In experiment 2, the addition of enzymes increased faecal concentration of propionate, acetate and total short-chain fatty acid (p<0.05) and tended to reduce post-prandial urea concentration (p=0.06). Although with similar digestibility, SBM shows a worse utilization of absorbed amino acids than the PM. Soybean oligosaccharides can beneficially change gut fermentation product formation. Enzymes can increase the gut fermentation activity and improve the SBM proteic value. © 2013 Blackwell Verlag GmbH.
Keywords: Cellulase; Oligosaccharides; Propionate; Protease; Protein; Urea response